XXXV aniversario del Consejo Mundial de la Paz - Enriquez, Rafael (Movimiento Cubano por la Paz y la Soberania de los Pueblos)
White flower, with doves as its petals Poster commemorating the 35th anniversary of the World Peace Council PO-0219